Racism, destitution and asylum - Jon Burnett (PAFRAS Briefing Paper Number 6, 2008)
The sixth of these briefing papers focuses on destitution and racist victimisation. In the 1998/99 year the Home Office began to record racially and religiously motivated harassment, wounding and assault. The total number of recorded incidences was 17,720. In 2006/7, the last year from when statistics were available, this had increased to 38,454. Statistics for offences against those seeking asylum are not recorded separately. But independent studies indicate that asylum seekers are particularly vulnerable to racist violence.